Effectiveness of Group Physical Exercise in Treating Major Depressive Disorder: An Analysis of Secondary Data from an Aborted Randomized Trial - Hossam Elgendy; Reham Shalaby; Belinda Agyapong; Deanna Lesage; Lacey Paulsen; Amy Delday; Sherianna Duiker; Shireen Surood; Yifeng Wei; Nnamdi Nkire; Vincent Israel Opoku Agyapong (Behavioral Sciences, 2024)
Background: Depression is highly prevalent and a significant cause of mortality and morbidity across the globe. Although antidepressants and/or psychotherapy are often used to treat depression, some recent studies indicate that exercise may play an important role in lowering depression symptoms among patients meeting the clinical criteria of a depressive episode. Objectives: This study aimed to evaluate the mental health and wellbeing of adult participants diagnosed with major depressive disorder (MDD) after fourteen weeks of receiving a supervised physical exercise program. Methods: In a pre-post design, the assessments were performed at baseline, seven weeks and fourteen weeks following the exercise intervention program using facilitated self-reported psychometric scales. The Beck Depression Inventory (BDI-2) and Clinical Outcomes in Routine Evaluation—Outcome Measure (CORE-OM) were used to assess depression. The short form of the International Physical Activity Questionnaire (IPAQ) was used for the self-reporting of participants’ physical activity. Results: At the beginning of the study, the baseline total mean scores and standard deviations for the BDI-2, CORE-OM, and IPAQ in both genders did not differ significantly (p-value > 0.05). Patients showed significant improvement in all assessment scales after completing fourteen weeks of the physical exercise program. Based on the BDI-2, the baseline score dropped from 31.25 (indicating moderate to severe depression) to 14.25 (indicating mild to minimal depression), with a p-value of <0.001. The CORE-OM total mean score was reduced from 1.91 to 0.98 with a significant p-value < 0.005 indicating effective clinical improvement in depression symptoms. The IPAQ total MET-minutes/week mean score increased from 1713.22 to 4367.62, indicating an improvement in the participants’ weekly P.E. intake; however, the change was not statistically significant (p = 0.07). Conclusions: Exercise treatment is linked with considerable therapeutic improvement in patients with MDD, particularly when exercise is sustained over time. The BDI-2 and CORE-OM total scores significantly decreased after the fourteen-week P.E. programme, indicating a change from moderate and severe depression to minimal and mild depression. Our findings offer insightful information to primary care doctors and psychiatrists, indicating that prescribing exercise to depressed patients may be a helpful adjunctive therapy.